Qur'an Calligraphy at The Straits of Malacca Mosque: Symbols, Meanings and Messages - Samsul Ariyadi; Muhammad Azizan Fitriana; Siti Shopiyah; Siti Rohmah; Mayadah Hanawi (Lembaga Bale Literasi, 2025)
This article aims to examine the function and role of Qur'anic calligraphy in the context of the Malacca Straits Mosque. This study is carried out by applying the semiotic and hermeneutic approach of Islam, which makes it possible to examine the symbols, meanings and messages contained in the calligraphy from various perspectives, including historical, social, and cultural contexts. With an analytical focus on the calligraphy of the main wall and the mihrab, this study seeks to uncover the symbolic and non-verbal communication aspects carried by sacred texts in the worship space. In addition to exploring how calligraphy functions as a medium of teaching and reminder of spiritual values, this article will also discuss the visual aesthetic impact produced by such calligraphy, as well as how these artistic elements are able to create a solemn atmosphere in worship. Within the framework of scientific research, this article is prepared with a systematic structure with a qualitative analysis approach and observation of photographs and calligraphy transcription used as the main method in understanding symbolic messages. The main focus of the study is on the calligraphy text found on the main wall and mihrab of the Malacca Strait Mosque, which is believed to represent the core of the religious messages to be conveyed. Through visual and textual analysis, this study will identify the relationship between calligraphy aesthetics and the spiritual experience of pilgrims, as well as explore how calligraphy functions as a community bond that strengthens the collective identity of Muslims in the region. This study also focuses on the aspect of calligraphy, as one of the highest art forms in Islam, in this mosque not only functions as a decorative element, but also as a medium of communication that is rich in meaning. Every indentation and dot in calligraphy illustrates the dynamics of the spirituality of Muslims in interpreting the Qur'an, where every word becomes a window that connects man with the divine. The results of this study are expected to add academic insight in the field of Islamic art studies as well as contribute new perspectives to the discourse of Islamic cultural heritage, by highlighting the importance of preservation and appreciation of the art of calligraphy in the modern context.